An Analysis of Respiratory System Test Subjects: A Complete and Structured Guide - Cici Nur Azizah; Ridwan Ridwan; Lia Zaradiva; Diki Koerniadi; Sunarto Arif Sura (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study aims to evaluate the quality of 20 biology summative assessment items on respiratory system material for class XII in nine high schools spread across Sumatra and Sulawesi during the odd semester of the 2024/2025 academic year. The research subjects involved 130 students, and data were collected through Google Form. The analysis was conducted using Anates software version 4.0.9, including the validity, reliability, difficulty level, differentiating power, and quality of item triggers. The results showed that 75% of the questions had good validity, while the other 25% required revision. The reliability value of 0.82 indicates high consistency. Most of the questions had a moderate level of difficulty (75%), while some questions needed to be adjusted to reach the ideal proportion. In terms of differentiating power, the majority of questions were able to differentiate between high and low ability learners effectively, although some questions required improvement. Excerpts analysis showed that most of the options functioned well, but the less effective exterminators needed revision. This study concludes that the items have good overall quality, but still require some improvement to increase accuracy and effectiveness as an evaluation instrument for biology learning.